Reduction in acidity and heavy metal concentrations of acid mine drainage with organic matter and coal fly ash treatments in two different reclaimed-mining soils - Bambang Joko Priatmadi; Meldia Septiana; Ronny Mulyawan; Akhmad R Saidy (Journal of Degraded and Mining Lands Management, 2023)
Organic matter (OM) has a very crucial role in the management of acid mine drainage (AMD) using a passive treatment system, although information on the use of this system in different reclaimed-mining soils (RMS) is very limited. Therefore, this study aimed to determine the effect of adding OM to RMS with different characteristics. It was carried out by adding only OM or in combination with coal fly ash (CFA) to two RMS with different characteristics (Palam and Cempaka Soils) and quartz sand (control) in a batch reactor experiment. This was followed by the incubation of the mixture of soil/quartz-OM or soil/quartz-OM-CFA at 60% water holding capacity for 15 days. After incubation, AMD slowly flowed into the reactor, and its pH in the reactor was monitored every day for 30 days, while the concentrations of Fe (iron), Al (aluminum), and Mn (manganese) were measured on the 30th day. The results showed that the application of OM on Palam Soil only increased AMD pH by 0.38 units, while Cempaka Soil and quartz sand increased by 4.83 and 5.36 units, respectively. The addition of OM to Cempaka Soil and quartz sand also showed a higher reduction in heavy metals concentration in AMD than those in Palam Soil. It was also discovered that the application of OM combined with CFA led to a higher improvement in AMD quality than only using OM. This study demonstrated that the effect of OM addition on increasing pH and decreasing metal concentration on AAT management with the passive treatment system is controlled by soil characteristics.